Design of Deflection Measuring System for Steel Frame Bridge Structure - Yoga Alif Kurnia Utama (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
According to data compiled from BNPB, it can be seen that disasters occurred in Indonesia from the period of January 1 to August 5, 2021; as many as 1677 natural disasters occurred in Indonesia. These disasters include floods, landslides, tornadoes, and earthquakes. These natural disasters took many victims of the disaster. In addition, the natural disasters that occurred destroyed the existing infrastructure in the area. Various damage to infrastructure has paralyzed the lives of residents in the area. This will be worse if the bridge is damaged because the transportation access point will be cut off. Therefore, this research will create a system to check the strength of a bridge that has a steel frame. This examination is carried out by measuring the deflection of the bridge frame, and the results are displayed through the LCD. This system measures a frame deflection by utilizing a strain gauge sensor. This measurement will be compared with measurements using the actual deflection measuring instrument, LVDT. The results show that this system's measurements produce a measurement error of 3.79%. In conclusion, this study shows that the system is quite good as a measuring instrument for deflection on a real steel truss bridge.